1964
DOI: 10.1111/j.1440-1827.1964.tb00674.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Study of Hypertensive Heart

Abstract: The pathologic findings of hypertensive hearts a r e represented by myocardial hypertrophy, especially those of the left ventricles, but hypertension without cardiac hypertrophy is not rare. The influence of hypertension is manifested not only as cardiac hypertrophy, but also as acceleration of coronary atherosclerosis.The present report is on some of the results of cardiac measurings, concerning hypertensive and non-hypertensive cases in Part I, and of the study on correlations between hypertension and corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1968
1968
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…Furthermore, the results of this study serve to quantitatively explain for the first time the irregular helical-shaped distribution of fatty and fibrous plaques in coronary artery reported by previous ex vivo studies [29][30][31][32], and hinted at by the WT patterns shown for the representative case in Fig. 2, where the high WT region seems to follow a helical distribution.…”
Section: Summary Of Findings and Their Implicationssupporting
confidence: 71%
“…Furthermore, the results of this study serve to quantitatively explain for the first time the irregular helical-shaped distribution of fatty and fibrous plaques in coronary artery reported by previous ex vivo studies [29][30][31][32], and hinted at by the WT patterns shown for the representative case in Fig. 2, where the high WT region seems to follow a helical distribution.…”
Section: Summary Of Findings and Their Implicationssupporting
confidence: 71%